2021
DOI: 10.3389/fmars.2021.666763
|View full text |Cite
|
Sign up to set email alerts
|

RNAi Reveals Role of Insulin-Like Androgenic Gland Hormone 2 (IAG2) in Sexual Differentiation and Growth in Hermaphrodite Shrimp

Abstract: Insulin-like androgenic gland hormone (IAG) is the most widely known hormone that regulates sexual differentiation in crustaceans. Previously, a transcriptome study described two transcripts of IAGs (Lvit-IAG1 and Lvit-IAG2) in the peppermint shrimp Lysmata vittata, a species characterized by a rare reproductive system of protandric simultaneous hermaphroditism (PSH). Herein, we explored the function of Lvit-IAG2 via RNA interference (RNAi) experiments, and then compared the functional differences between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
3
19
1
Order By: Relevance
“…The following may explain these apparently contradictory results. Previous studies suggested that Lvit-IAG2 is more than a sexual differentiation regulator, and it also stimulates the growth of the PSH species (Liu et al, 2021a). In the present study, silencing the Lvit-CFSH1a gene impeded individual growth of the species.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The following may explain these apparently contradictory results. Previous studies suggested that Lvit-IAG2 is more than a sexual differentiation regulator, and it also stimulates the growth of the PSH species (Liu et al, 2021a). In the present study, silencing the Lvit-CFSH1a gene impeded individual growth of the species.…”
Section: Discussionsupporting
confidence: 56%
“…Nevertheless, two IAG genes were identified in the PSH shrimp L. vittata, and they cooperatively modulated male sexual differentiation of the species (Liu et al, 2021a,b). Specifically, Lvit-IAG1 was suggested to be closely related to the development of both AM and male gonopores, and participated in primary-tosecondary spermatocyte transition (Liu et al, 2021b); whereas Lvit-IAG2 was somewhat related to the development of AM, and participated in secondary spermatocyte-to-spermatid transition (Liu et al, 2021a). In the present study, results of short-term silencing experiment and rLvit-CFSH1a injection experiment demonstrated that Lvit-CFSH1a acted as an inhibitor of Lvit-IAG2 rather than Lvit-IAG1.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of sexual differentiation and development in crustacean species is a complicated biological process, which has received great attention in recent years. To the best of our knowledge, IAG was the most important gene, which was reported to positively regulate the male sexual differentiation and testis development in many crustacean species ( Li et al, 2012 ; Ventura et al, 2012 ; Huang et al, 2014 ; Li et al, 2015 ; Liu et al, 2021 ; Zhou et al, 2021 ). However, the mechanism of gonad differentiation and development in crustaceans.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like androgenic gland hormone ( IAG ) is the main focused gene, produced by the androgenic gland ( Ventura et al, 2009 ; Rosen et al, 2010 ; Ventura et al, 2011 ). It has been proven to play essential roles in promoting male sex-determination and sex-differentiation in most crustacean species, including Fenneropenaeus chinensis ( Li et al, 2012 ), Scylla paramamosain ( Huang et al, 2014 ), Hermaphrodite Shrimp ( Liu et al, 2021 ), Fenneropenaeus merguiensis ( Zhou et al, 2021 ), and M. nipponense ( Li et al, 2015 ). Silencing of IAG in male M. rosenbergii by RNA interference may also lead to complete sex reversal ( Ventura et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin-like androgenic gland hormone (IAG) is the main gene expressed and analyzed in the androgenic gland (Ventura et al, 2009(Ventura et al, , 2011Rosen et al, 2010). It has been shown to play essential roles in promoting male sex determination and sex differentiation in most crustacean species, including Fenneropenaeus chinensis (Li et al, 2012), Scylla paramamosain (Huang et al, 2014), Lysmata vittata (Liu et al, 2021), Fenneropenaeus merguiensis (Zhou et al, 2021), and M. nipponense (Li et al, 2015a). Silencing of IAG in male M. rosenbergii by RNA interference (RNAi) may also lead to a complete sex reversal (Ventura et al, 2012).…”
Section: Introductionmentioning
confidence: 99%